2019
DOI: 10.1038/s41416-019-0695-z
|View full text |Cite|
|
Sign up to set email alerts
|

DKC1 enhances angiogenesis by promoting HIF-1α transcription and facilitates metastasis in colorectal cancer

Abstract: Background Dyskeratosis congenita 1 (DKC1) is dysregulated in several cancers. However, the expression and function of DKC1 in colorectal cancer (CRC) is rarely reported. Methods Tissue microarrays (TAMs) including 411 cases of CRC tissues and corresponding paracancerous tissues were used to examine the DKC1 expression. The correlations between the DKC1 expression and clinicopathological or survival characters were further analysed. The functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 50 publications
2
48
1
Order By: Relevance
“…Dyskeratosis congenita 1 is dysregulated across several cancers. In colorectal cancer (CRC), DKC1 stimulates angiogenesis and metastasis by stimulating HIF-1α and VEGF expression 62 . In addition to VEGF, HIFs also modulate angiogenic growth factor levels, including platelet-derived growth factor B, stromal-derived factor-1, and placenta growth factor 55 .…”
Section: Role Of Hifs In Tumor Progressionmentioning
confidence: 99%
“…Dyskeratosis congenita 1 is dysregulated across several cancers. In colorectal cancer (CRC), DKC1 stimulates angiogenesis and metastasis by stimulating HIF-1α and VEGF expression 62 . In addition to VEGF, HIFs also modulate angiogenic growth factor levels, including platelet-derived growth factor B, stromal-derived factor-1, and placenta growth factor 55 .…”
Section: Role Of Hifs In Tumor Progressionmentioning
confidence: 99%
“…These genes were distributed in multiple pathways ( Figure S1A, Supporting Information), and some of them, such as MET [19] (ranked 1st), PRKDC [20] (ranked 8th), EXO1 [21] (ranked 14th), and TM4SF1 [22] (ranked 25th), have been reported to promote tumor cell proliferation ( Figure 1C). Among the top nine genes (Table S1, Supporting Information), five genes have been reported to affect CRC progression (MET, [19] DKC1, [23] GRHL3, [24] PRKDC, [20] and GPC4 [25] ). We individually silenced the remaining four genes (WER75, FAIM, GCSH, and TEX10) with two independent synthesized small interfering RNAs (siR-NAs) in HT29 cells ( Figure S1B, Supporting Information) and we found that the knockdown of TEX10, which ranked 7th in the aberrant expression analysis and was identified as an essential gene in the shRNA library screening (Table S1, Supporting Information), had the highest inhibitory efficacy on the growth of HT29 cells ( Figure S1C, Supporting Information).…”
Section: Screening Indicates That Tex10 Is Upregulated and Is Associamentioning
confidence: 99%
“…BOP1 is a direct transcription target of β-catenin/TCF4, which induced cell migration and experimental metastasis of CRC cells ( Qi et al, 2016 ). DKC1 may regulate CRC angiogenesis and metastasis by directly activating HIF-1α transcription ( Hou et al, 2020 ). Ji et al (2019) showed that PTBP2 could elevate translational levels of RUNX2, which plays a vital role in CRC metastasis.…”
Section: Discussionmentioning
confidence: 99%